Special Economic Zones for the Digital Economy - Abdurakhmanov Abdulaziz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Many countries have also created specialized enclaves (physical and virtual) to boost digital commerce and innovation. In many ways, these parallel the role played by Special Economic Zones (SEZs) in manufacturing. By providing SEZ firms with superior infrastructure – and exempting them from many levies and procedures – such zones helped many countries boost manufacturing FDI, exports and innovation.